A Naturally Occurring Variation in the Proline-Rich Region Does Not Attenuate Human Immunodeficiency Virus Type 1 Nef Function - Rücker, Elke (American Society for Microbiology, 2004)
We analyzed human immunodeficiency virus type 1 (HIV-1) Nef variants to further evaluate the functional relevance of the R71T substitution previously proposed to attenuate viral replication (Fackler et al., Curr. Biol. 11:1294-1299, 2001). Our results demonstrate that this variation in the proline-rich region does not significantly affect the functional activity of Nef or HIV-1 infectivity or replication.